Uruguay : Report on the Observance of Standards and Codes on Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This report provides a summary of the level of observance with the Financial Action Task Force (FATF) and recommendations to strengthen their observance. IMF staff reviewed the institutional framework, relevant laws, regulations, guidelines, and other requirements to deter money laundering (ML) and financing of terrorism (FT) through financial institutions (FIs) and designated nonfinancial businesses and professions (DNFBPs). The assessment is based on the information available at the time of the on site visit by the team. During the mission, there was one ML prosecution under way, but previously there had been no ML prosecutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet